2010
DOI: 10.1038/hr.2010.244
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of glomerular filtration rate estimated by the Japanese equation among patients who underwent complete coronary revascularization

Abstract: An equation that accurately estimates the glomerular filtration rate (GFR) in the Japanese population has been proposed; however, the prognostic significance of estimated GFR (eGFR) defined according to this equation has not been reported. In addition, the prognostic significance of eGFR during long-term follow-up after complete coronary revascularization remains unclear. We assessed the prognostic significance of eGFR values, estimated by the new Japanese equation, in a cohort of patients following complete c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The results of these studies have found that, compared to patients with normal renal function, the risk for cardiovascular events, including cerebrovascular disease, cardiac death, and total mortality increases by 2–3-fold in those with CKD even when the CKD is mild. It has been reported that the risk increases in association with the severity of the disease 740 , 769 , 770 ) . In addition, according to the observational CREDO-Kyoto study, the risk for cardiovascular death is 2.9-fold higher for post-PCI patients with CKD, and the risk for total mortality increases by 2.1-fold 183 ) .…”
Section: Comprehensive Risk Managementmentioning
confidence: 99%
“…The results of these studies have found that, compared to patients with normal renal function, the risk for cardiovascular events, including cerebrovascular disease, cardiac death, and total mortality increases by 2–3-fold in those with CKD even when the CKD is mild. It has been reported that the risk increases in association with the severity of the disease 740 , 769 , 770 ) . In addition, according to the observational CREDO-Kyoto study, the risk for cardiovascular death is 2.9-fold higher for post-PCI patients with CKD, and the risk for total mortality increases by 2.1-fold 183 ) .…”
Section: Comprehensive Risk Managementmentioning
confidence: 99%
“…eGFR for patients with a baseline eGFR less than 30 mL/min/1.73 m² was also analysed. eGFR (in mL/min/1.73 m²) was calculated using the serum creatinine-based formula (Modification of Diet in Renal Disease) for adults, 11 the Japanese equation for Japanese adults, 12 and the modified Schwartz equation for adolescents. 13 …”
Section: Methodsmentioning
confidence: 99%
“…Khaw reported that increasing HbA1c levels are associated with allcause and CV mortality in non-diabetic patients 32) . In that an increase in HbA1c of 1 percentage point was associated with a relative risk of all-cause mortality of than in those without CKD (eGFR ≥ 90 ml/min/1.73 m 2 ), suggesting that the risk of a CV event increases with worsening eGFR values [21][22][23] . Renal dysfunction could be one of the key factors associated with CV events despite aggressive lipid lowering therapy with statins 9) .…”
Section: Glycemic Control As a Residual Riskmentioning
confidence: 99%